1995
DOI: 10.1073/pnas.92.9.3726
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and cytotoxic effects of camptothecin, a topoisomerase I inhibitor, on trypanosomes and Leishmania.

Abstract: Parasites pose a threat to the health and lives of many millions of human beings. Among the pathogenic protozoa, Trypanosoma brucei, Trypanosoma cruzi, and Leishmania donovani are hemoflagellates that cause particularly serious diseases (sleeping sickness, Chagas disease, and leishmaniasis, respectively). The drugs currently available to treat these infections are limited by marginal efficacy, severe toxicity, and spreading drug resistance. Camptothecin is an established antitumor drug and a well-characterized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
108
0
4

Year Published

2003
2003
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(117 citation statements)
references
References 43 publications
5
108
0
4
Order By: Relevance
“…Camptothecin enhances the formation of covalent complexes (Fig. 3, lane 2), consistent with our previous studies of cleavable complex formation in trypanosomes (13). Under these conditions, enhancement of cleavable complex formation by camptothecin is comparable for T. brucei and human enzymes (1.7-fold and 2.1-fold, respectively).…”
Section: Validation Of Small Subunit As Catalyticsupporting
confidence: 91%
See 1 more Smart Citation
“…Camptothecin enhances the formation of covalent complexes (Fig. 3, lane 2), consistent with our previous studies of cleavable complex formation in trypanosomes (13). Under these conditions, enhancement of cleavable complex formation by camptothecin is comparable for T. brucei and human enzymes (1.7-fold and 2.1-fold, respectively).…”
Section: Validation Of Small Subunit As Catalyticsupporting
confidence: 91%
“…When disrupted (e.g., by SDS or alkali) such complexes yield a denatured enzyme covalently linked, via the active site tyrosine, to the 3Ј end of the enzyme-induced break in substrate DNA. In previous work with African trypanosomes we found that camptothecin promotes the formation of covalent protein-DNA complexes with both nuclear and mitochondrial DNA, and inhibits DNA biosynthesis (13). Furthermore, it is cytotoxic to three pathogenic kinetoplastids: T. brucei, T. cruzi, and L. donovani.…”
mentioning
confidence: 94%
“…Previous studies have shown that CPT treatment promotes stabilization of the cleavable complex with both nuclear as well as kinetoplast DNA. 23 Very little is known about the signalling pathway downstream of the formation of cleavable complex, which ultimately leads to increase in the number of apoptotic cells. In the present study, CPT-induced cytotoxic lesion inside leishmanial cells appears to inhibit the mitochondrial respiration, which is followed by an increase in mitochondrial membrane potential.…”
Section: Discussionmentioning
confidence: 99%
“…22 CPT, like other potential antileishmanial agents, has been shown to inhibit type I DNA topoisomerase of Leishmania donovani. 23 However, it is still unclear how the stabilization of topo I-DNA covalent complex and subsequent induction of DNA strand breaks lead to cytotoxicity in leishmanial cells.…”
Section: Introductionmentioning
confidence: 99%
“…41 Camptothecin 47, a pentacyclic alkaloid from Camptotheca acuminata (Nyssaceae), is a well known antitumor agent and a specific inhibitor of human DNA topoisomerase I. Bodley et al have shown that 47 also inhibits the nuclear and mitochondrial topoisomerase I of T. b. brucei thus blocking DNA replication and inducing the death of bloodstream trypomastigotes (IC 50 = 1.6 µM). 42 In a study of a series of camptothecin analogs, the 9-substituted-10,11-methylenedioxy derivatives were significantly more active on T. b. brucei bloodstream trypomastigotes than the parent compound and retained as intracellular target the parasites' topoisomerase I. For example, 9-chloro-10,11-methylenedioxycamptothecin 48 was 40 times more trypanocidal than 47 (IC 50 = 0.041 µM).…”
Section: Alkaloidsmentioning
confidence: 99%